Correlation Between Introvert-Extrovert Personality and Students’ Speaking Ability - Khotimah, Husnul; Saputri, Tiyas (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2021)
This study was an attempt to investigate the possible effect of introverted-extroverted personality on students' speaking ability performance. The objective of this study were (1) to analyze the significant correlation between students' personality (introvert -extrovert) and their speaking ability performance (2) To find out the speaking ability performance of students’ introvert personality, and (3) To find out the speaking ability performance of students’ extrovert personality. The method used in this study is meta-analysis. The data were calculated statistically by Jamovi. The result of this study showed the correlation between introvert-extrovert personality in speaking ability performance is 1.27 which indicates a high correlation between these variables. The study also found that extroverts speak better than introverts. From this study, the researcher concluded that introvert and extrovert personality affected students' performance of English speaking skills.